Psychological impact of the COVID-19 pandemic on dental health personnel in Norway - M. M. Uhlen; V. E. Ansteinsson; L. Stangvaltaite-Mouhat; L. Korzeniewska; R. Skudutyte-Rysstad; M. Shabestari; I. Mdala; E. A. S. Hovden (BMC, 2021)
Abstract Background The SARS-CoV-2 pandemic put a pressure on all healthcare professionals and has affected the delivery of health care services globally. There is a need to understand the impact on different health care professionals in different countries. The aim of the present study was to explore the psychological impact of the pandemic among dental staff in Norway in relation to background characteristics, work situation and preparedness of the service. Methods A structured questionnaire sent electronically to dentists, dental hygienists and dental assistants inquired information about the lockdown period in Norway (13 March-17 April 2020). Distributions of background characteristics, perceptions of preparedness and psychological impact were calculated. Exploratory factor analysis was performed, and Structural Equation Models (SEMs) were used to compare psychological impact between dental professionals treating patients versus not during lockdown. Results Among the 1237 respondents, 58.8% worked clinically with patients. The majority were concerned of becoming infected (71.9%), of infecting others (85.4%) and/or of their family becoming infected (76.9%). Respondents who treated patients felt significantly more insecure about whether having become infected or not. The minority felt discriminated (6.7%), worried about death (11.7%), felt that life was threatening (9.8%) or felt loss of control of their lives (8.9%). More than 80% agreed that their workplace handled the situation well. Four factors were retrieved from the factor analysis. SEMs showed that gender and work experience had a significant effect on the factors Instability, Infection and Concerns. Respondents with work experience ≥10 years were less likely to express fear about Instability and Infection. Personnel reporting that their workplace had adequate equipment were also less concerned, however having adequate equipment did not reduce the factor Loss of control. Conclusion The present study showed a considerable psychological impact of the COVID-19 pandemic on dental personnel in Norway regardless of working clinically with patients or not. However, working with patients increased the insecurity about own infection status and of infecting people close to them. A safe working environment and adequate infection control measures are associated with less fear of infection and feeling of instability.